Peat as a source of nitrogen for plants in pot culture - Kivinen, Erkki; Kaila, Armi (Agricultural and Food Science, 1958)
Results are reported of a pot experiment in which four successive oat crops were grown with peat as the only source of nitrogen. Eight samples from virgin peat lands representing different land qualities were used. The samples were air-dried and ground which is known to increase markedly the amount of ammonium nitrogen in peat. Some data from incubation experiments were compared with the uptake of peat nitrogen by plants. The results did not agree with the earlier conception that the Carex-peats are superior to the Sphagnum-peats, particularly in regard to the availability of peat nitrogen. Under the conditions of pot culture and incubation experiments some of the fairly poor Carex-Sphagnum peats were markedly better as supplyers of nitrogen to the plants than were e.g. samples of Bryales-Carex peat and eutrophic Sphagnum-Carex peat of the present study. The uptake of nitrogen by plants from the peat samples was often lower than the amounts of mineral nitrogen accumulated in short-time incubation experiments. The possible reasons for this discrepance was discussed. It was pointed out that in pot experiments these air-dried and ground peat proved to produce higher yields without phosphorus fertilizers than without application of nitrogen, at least in the first year.